P686 Outcomes of COVID-19 among patients with inflammatory bowel diseases and the influence of IBD-related medications– A Danish prospective population-based cohort study. (21st January 2022) - Attauabi, M; Dahlerup, J F; Poulsen, A; Rosager Hansen, M; Vester-Andersen, M K; Eraslan, S; Prahm, A P; Pedersen, N; Larsen, L; Jess, T; Neumann, A; Haderslev, K V; et al.
Abstract: Background: Population-based data regarding outcomes of coronavirus disease 2019 (COVID-19) among patients with ulcerative colitis (UC) and Crohn's disease (CD) remain limited. Methods: We conducted a population-based study investigating the outcomes of COVID-19 among patients with UC and CD in Denmark. The Danish COVID-19 IBD Database is an extensive population-based database which prospectively monitors the disease course of laboratory-confirmed COVID-19 among patients with UC and CD. Severe COVID-19 was defined as COVID-19 necessitating intensive care unit admission, ventilator use, or death, while adverse COVID-19 was defined as requirement of COVID-19 related hospitalization. Regression analysis was adjusted for age, sex, disease type, disease activity, cardiovascular disease, and corticosteroids. Outcomes of COVID-19 among patients with UC and CD were compared with those among the background population covering all incidents of COVID-19 in Denmark. Results: The study included 319 patients with UC and 197 patients with CD from January 28 th, 2020, to April 1 st, 2021. Baseline characteristics are presented in Table 1. A significantly higher risk of COVID-19-related hospitalization was observed among patients with UC (N=46(14.4%), RR=2.49 (95%CI 1.91–3.26)) and CD (N=24(12.2%), RR=2.11 (95%CI 1.45–3.07)) as compared with the background population (N=13, 306 (5.8%)). A similar pattern was observed for admission to intensive care (UC: N=8(2.51%), RR=27.88 (95%CI 13.88–56.00); CD: N=3 (1.52%), RR=16.92 (95%CI 5.46–52.46)) (Figure 1). The association between these outcomes and IBD-related clinical characteristics and treatments is presented in Tables 2–3. As shown, none of the IBD-related medications were associated with severe COVID-19 in univariate and multivariable analysis. However, systemic steroids were found to be associated with an increased risk of adverse COVID-19 among patients with CD (adjusted odds ratio (aOR)=13.62 (95% CI 1.98–17.77)). Conclusion: This Danish population-based study on COVID-19 outcomes among patients with UC and CD demonstrated severe COVID-19 among only a minority of patients, which was not associated with IBD-related medications. Apart from systemic steroids, this study encourages continued use of IBD therapy to prevent IBD relapse and complications.